TT virus in peripheral blood cells from patients with human papillomavirus (HPV): investigating association with cervical carcinoma - Suzuki,Patrícia Sayuri (2014)
Torque Teno Virus (TTV) presence was investigated in peripheral blood of 117 brazilian women by nested polymerase chain reaction. TTV DNA was observed in 18.6% of healthy donors and in 24.32% Human Papillomavirus (HPV) patients. TTV presence was also investigated in the HPV positive group for comparison between the cervical cancer and noncancerous patients. TTV DNA prevalence was significantly higher among the HPV positive patients with cervical cancer (57.14%) than in HPV noncancerous patients (16.67%). Thus, the presence of TTV infection could be a risk factor for cancer development in the patients presenting HPV-TTV coinfection. Further studies are required to clarify the TTV influence in HPV pathogenesis.